The Convergence of Dopamine and α-Synuclein: Implications for Parkinson's Disease. (6th March 2018) - Mor, Danielle E; Ischiropoulos, Harry
In Parkinson's disease (PD), the loss of dopamine-producing neurons in the substantia nigra (SN) leads to severe motor impairment, and pathological inclusions known as Lewy bodies contain aggregated α-synuclein protein. The relationship of α-synuclein aggregation and dopaminergic degeneration is unclear. This commentary highlights a recent study showing that the interaction of α-synuclein with dopamine may be an important mechanism underlying disease. Elevating dopamine levels in mice expressing human α-synuclein with the A53T familial PD mutation recapitulated key features of PD, including progressive neurodegeneration of the SN and decreased ambulation. The toxicity of dopamine was dependent on α-synuclein expression; hence, raising dopamine levels in nontransgenic mice did not result in neuronal injury. This interaction is likely mediated through soluble α-synuclein oligomers, which had modified conformations and were more abundant as a result of dopamine elevation in the mouse brain. Specific mutation of the dopamine interaction motif in the C-terminus of α-synuclein rescued dopamine neurons from degeneration in Caenorhabditis elegans models. Here, these findings are discussed, particularly regarding possible mechanisms of oligomer toxicity, relevance of these models to sporadic and autosomal recessive forms of PD, and implications for current PD treatment.